Penerapan Material Ramah Lingkungan dalam Arsitektur Modern di Indonesia - Rizqi Maulana Azhari; M.Lukman Ery Nanda Panjaitan (PT. AHLAL PUBLISHER NUSANTARA, 2025)
The development of architecture in Indonesia is increasingly required to respond to environmental issues at both global and local levels. This study seeks to examine the use of environmentally friendly materials (green materials) in modern Indonesian architecture by highlighting its trends, motivations, challenges, and implications. The research was carried out using a qualitative method through a literature review of publications indexed in Scopus and Sinta over the past ten years, complemented by an analysis of several building case studies in Indonesia. The findings indicate a growing utilization of environmentally friendly materials, which can be categorized into: recycled materials, such as recycled concrete and pressed bricks made from waste; renewable natural materials with minimal processing, such as bamboo, certified wood, and ecobricks; innovative technology-based materials, including rice husk panels and coconut-fiber composites; and vernacular materials revitalized in contemporary practice. The motivations behind their application are not only related to sustainability efforts and energy efficiency but also encompass culturally rooted aesthetic considerations and the need to meet green building standards. Nevertheless, several challenges remain, including limited supply chains, the perception of relatively high initial costs, suboptimal supporting regulations, and the need to enhance the technical competence of practitioners. Overall, this article emphasizes that integrating environmentally friendly materials into modern Indonesian architecture has the potential to strengthen the creation of contextual, sustainable, and locally rooted architectural works while contributing to the reduction of environmental impacts. To accelerate the transition toward green architectural practices, policy support, the development of local material industries, expanded research, and the strengthening of architectural education are needed. Keywords: Environmentally Friendly Materials, Sustainable Architecture, Modern Indonesian Architecture, Green Buildings, Green Construction Materials. Abstrak Perkembangan arsitektur di Indonesia semakin dituntut untuk memberikan respons terhadap persoalan lingkungan, baik pada tingkat global maupun lokal. Kajian ini berupaya menelaah penggunaan material ramah lingkungan (green material) dalam arsitektur modern Indonesia dengan menyoroti tren, motivasi, hambatan, serta implikasinya. Penelitian dilakukan melalui metode kualitatif dengan telaah literatur terhadap publikasi terindeks Scopus dan Sinta selama sepuluh tahun terakhir, disertai analisis beberapa studi kasus bangunan di Indonesia. Temuan penelitian menunjukkan adanya peningkatan pemanfaatan material ramah lingkungan, yang dapat dikelompokkan menjadi: material hasil daur ulang, seperti beton daur ulang dan batu bata press berbahan limbah; material alami terbarukan dengan proses pengolahan minimal, seperti bambu, kayu bersertifikasi, dan ecobrick; material inovatif berbasis teknologi, misalnya panel sekam padi dan serat dari sabut kelapa; serta material vernakular yang kembali dihidupkan dalam praktik kontemporer. Motivasi penerapannya tidak hanya berkaitan dengan upaya keberlanjutan dan efisiensi energi, tetapi juga mencakup aspek estetika berbasis budaya serta kebutuhan pemenuhan standar bangunan hijau. Kendati demikian, sejumlah tantangan masih ditemukan, antara lain keterbatasan rantai pasok, persepsi biaya awal yang relatif tinggi, belum optimalnya regulasi pendukung, serta kebutuhan akan peningkatan kompetensi teknis para praktisi. Secara keseluruhan, artikel ini menegaskan bahwa integrasi material ramah lingkungan dalam arsitektur modern Indonesia berpotensi memperkuat penciptaan karya arsitektur yang kontekstual, berkelanjutan, dan memiliki identitas lokal, sekaligus berkontribusi pada pengurangan dampak lingkungan. Untuk mempercepat transisi menuju praktik arsitektur hijau, diperlukan dukungan kebijakan, pengembangan industri material lokal, perluasan riset, serta penguatan pendidikan arsitektur. Kata kunci: Material Ramah Lingkungan, Arsitektur Berkelanjutan, Arsitektur Modern Indonesia, Bangunan Hijau, Material Konstruksi Hijau.